Simulation of Inhomogeneous Columns of Beads under Vertical Vibration. (22nd April 2009) - Carneiro, Marcus V.; Barroso, Joaquim J.; Macau, Elbert E. N.
Abstract : We present results from computational experiments of one-dimensional inhomogeneous granular column. With characteristic properties lying between those of liquids and solids, this class of material consists of assemblies of solid particles which interact via mechanical forces (contact and friction) and are maintained together by a gravitational field. The system is composed of a vertical column of spherical beads driven by a sinusoidally vibrating plate. Results for 10 bead experiments show the fluidization and condensation phenomena, both dependent on the amplitude and frequency of the driving plate. Some scaling properties arising from the dynamics of the beads are also shown.